2013
DOI: 10.15835/nbha4129218
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tolerance of Citrus (<i>Citrus tangerina</i>) Seedlings to Soil Water Deficit after Mycorrhizal Inoculation: Changes in Antioxidant Enzyme Defense System

Abstract: Arbuscular mycorrhizal fungi (AMF) can enhance tolerance of plants to soil water deficit, whereas morphological observations of reactive oxygen species and antioxidant enzyme system are poorly studied. The present study thereby evaluated temporal variations of the antioxidant enzyme system in citrus (Citrus tangerina) seedlings colonized by Glomus etunicatum and G. mosseae over a 12-day period of soil drying. Root colonization by G. etunicatum and G. mosseae decreased with soil drying days from 32.0 to 1.0% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(30 reference statements)
1
8
0
Order By: Relevance
“…According to the results of Tian et al (2013) , inoculation with AMF increased CAT activity of Plukenetia volubilis plants under DS, thus reducing both accumulation of H 2 O 2 and oxidative damage to lipids. Another study by Ni et al (2013) showed significantly higher leaf SOD and root CAT activity in mycorrhizal citrus tangerine seedlings as compared with non-mycorrhizal seedlings under DS conditions. Our study further showed that amongst SODs, leaf Cu/Zn-SOD, and Mn-SOD activities under mycorrhization remained unchanged under WW conditions, but significantly increased by 35 and 174% under DS conditions, respectively, as compared with non-mycorrhization ( Table 3 ).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…According to the results of Tian et al (2013) , inoculation with AMF increased CAT activity of Plukenetia volubilis plants under DS, thus reducing both accumulation of H 2 O 2 and oxidative damage to lipids. Another study by Ni et al (2013) showed significantly higher leaf SOD and root CAT activity in mycorrhizal citrus tangerine seedlings as compared with non-mycorrhizal seedlings under DS conditions. Our study further showed that amongst SODs, leaf Cu/Zn-SOD, and Mn-SOD activities under mycorrhization remained unchanged under WW conditions, but significantly increased by 35 and 174% under DS conditions, respectively, as compared with non-mycorrhization ( Table 3 ).…”
Section: Resultsmentioning
confidence: 93%
“…Mycorrhization associated changes in antioxidant enzymes are widely reported ( Hu et al, 2007 ; Ni et al, 2013 ). Earlier studies ( Ni et al, 2013 ; Wu et al, 2013 ) using different citrus species demonstrated that the AMs conferred greater tolerance to plants against soil water deficit through an enhancement in their antioxidant enzyme defense system consequent upon a decrease in level of H 2 O 2 and . In our studies, the DS induced accumulation of leaf and H 2 O 2 concentration, regardless of AMF- or non-AMF-seedlings ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies indicated that the low H 2 O 2 and MDA accumulation observed in AM plants was correlated with water stress tolerance [39,81,83]. Reduced H 2 O 2 and MDA content in AM plants might be due to better water availability and osmoregulation and higher antioxidative defense systems [43,84,85]. In the present study, higher leaf water, ion homeostasis, and osmotic organic content in AM plants were associated with lower accumulation of H 2 O 2 and MDA, indicating lower oxidative damage in the colonized plants.…”
Section: Discussionmentioning
confidence: 99%
“…Mycorrhization associated changes in antioxidant enzymes are widely reported. Earlier studies (Ni et al 2013 andHuang et al 2014) The less oxidative damage in AMF inoculated plants might be due to better water avail ability and osmoregulation and high er antioxidative defense systems (Ni et al 2013.…”
Section: Effect Of Drought Stress and Amf On Oxidative Stressmentioning
confidence: 99%